Comparing the effectiveness of a brief intervention to reduce unhealthy alcohol use among adult primary care patients with and without depression: A machine learning approach with augmented inverse probability weighting. (1st October 2022) - Papini, Santiago; Chi, Felicia W.; Schuler, Alejandro; Satre, Derek D.; Liu, Vincent X.; Sterling, Stacy A.
Abstract: Background: The combination of unhealthy alcohol use and depression is associated with adverse outcomes including higher rates of alcohol use disorder and poorer depression course. Therefore, addressing alcohol use among individuals with depression may have a substantial public health impact. We compared the effectiveness of a brief intervention (BI) for unhealthy alcohol use among patients with and without depression. Method: This observational study included 312, 056 adult primary care patients at Kaiser Permanente Northern California who screened positive for unhealthy drinking between 2014 and 2017. Approximately half (48%) received a BI for alcohol use and 9% had depression. We examined 12-month changes in heavy drinking days in the previous three months, drinking days per week, drinks per drinking day, and drinks per week. Machine learning was used to estimate BI propensity, follow-up participation, and alcohol outcomes for an augmented inverse probability weighting (AIPW) estimator of the average treatment (BI) effect. This approach does not depend on the strong parametric assumptions of traditional logistic regression, making it more robust to model misspecification. Results: BI had a significant effect on each alcohol use outcome in the non-depressed subgroup (−0.41 to −0.05, all p s < .003), but not in the depressed subgroup (−0.33 to −0.01, all p s > .28). However, differences between subgroups were nonsignificant (0.00 to 0.11, all p s > .44). Conclusion: On average, BI is an effective approach to reducing unhealthy drinking, but more research is necessary to understand its impact on patients with depression. AIPW with machine learning provides a robust method for comparing intervention effectiveness across subgroups. Highlights: Unhealthy drinking and depression together are associated with adverse outcomes. Brief intervention (BI) for unhealthy drinking was delivered in primary care. Effectiveness was assessed using flexible and robust machine learning methods. On average BI was an effective approach to reducing unhealthy drinking. There was a pattern of results suggesting less benefit for depressed patients.